Karl Marx's Socialist Economic Perspective Compared To Umar Bin Abdul Aziz's Islamic Economic Thoughts On Social Justice - Pephitasya Juliana; Selfa Rosmita; Siradjuddin (LP2M IAIN Palopo, 2025)
The concept of social justice in societal development. Karl Marx, through his socialist economic theory, highlighted the inequality born of the capitalist system, while Umar bin Abdul Aziz, in the Islamic economic tradition, emphasized the principle of equitable distribution of wealth based on sharia values. This study aims to compare the thoughts of Karl Marx and Umar bin Abdul Aziz from a social justice perspective, while identifying common ground and conceptual differences between the two. The study employed a qualitative approach through library research. The analysis was conducted using a comparative-descriptive method. The analysis shows that Karl Marx rejected capitalism because it resulted in class exploitation and proposed the abolition of private ownership of the means of production in order to create a classless society. In contrast, Umar bin Abdul Aziz maintained the recognition of individual ownership but emphasized distributive justice through zakat, taxes, and redistribution policies. The similarities between the two lie in the goal of creating social justice, but fundamentally different in their ideological foundations: Marx's origins stem from historical materialism, while Umar bin Abdul Aziz's is based on monotheism and Islamic law. This comparison of the thoughts of Karl Marx and Umar bin Abdul Aziz demonstrates that social justice can be understood from both secular and religious perspectives. Marx's thought offers a structural critique of capitalism, while Umar bin Abdul Aziz presents solutions rooted in moral and religious values. Both make important contributions to contemporary social justice discourse